عقد المضاربة وإمكانية تطبيقه في المصارف الإسلامية مع إشارة خاصة لرؤية محمد باقر الصدر (المجلة العراقية للعلوم الاقتصادية, 2018)
The objective of this research is to monitor the use of investment contract in Islamic banks and stand on the problems and obstacles that prevent it is application with grate significant in some of these banks through the premise that, the possibility of increasing the use of investment contract in Islamic banks after the reduction of problems and constraints used in these banks , also can be applied the ideas of Mr. Mohammed Baqir al-Sadder with respect to the investment contract contained in each of the processors contained reservations as reasons for not taking speculative formula of Islamic banking. In conclusion that reached from the research, it found the possibility of increasing the use of investment contract after the success of its use in some Islamic banks, as can the application of Mr. Sadri's ideas for a speculation in the dissertation Bank Ellerbe in Islam after the risk reduction resulting from this contract at these banks. so, the recommendation of this research including reliance on the wording of speculation, because it is a formula consistent with the development of domestic economic performance in Islamic Economics, for reducing the work modes: the other, especially Murabaha mode because the distortion of the philosophy of Islamic banking is enough to reflect on the Islamic system as a whole, as well as work to reduce the risk of the application form of speculation in order to increase reliability in the recruitment of resources, especially after it became clear through research that some Islamic banks which have expanded the use of investment contract has achieved financial returns and profitable high reflected on the increase in production capacity and raise the developmental role of these banks in their countries.